Ultralight high-strength and high-plasticity dual-phase magnesium-lithium alloy and preparation process and application thereof

Through high vacuum electromagnetic induction melting and composite deformation process, a dual-phase magnesium-lithium alloy with high strength and good plasticity is prepared, which solves the problem of low absolute strength of dual-phase magnesium-lithium alloy and meets the performance requirements in aerospace, transportation and other fields. Require.

CN119351840APending Publication Date: 2025-01-24DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411470629.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Dual-phase magnesium lithium alloys with a content of more than 6% Li have a problem of low absolute strength, which seriously restricts their use in engineering applications.

Method used

Dual-phase Mg-Li-Al-Zn-Gd-Y-Ca magnesium-lithium alloy is prepared by high-vacuum electromagnetic induction melting method, and the fine grain size is optimized through a composite deformation process of multi-directional forging, temperature-changing rapid extrusion and room temperature rolling. Chemicalization and organizational structure to improve the mechanical properties of the alloy.

Benefits of technology

The high strength and good plasticity of the alloy, the density is 1.55-1.65g/cm3, the tensile strength is 300-360 MPa, the yield strength is 280-340MPa, and the extension rate is 12-25 %. It is suitable for aerospace, transportation, etc. field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351840A_ABST
    Figure CN119351840A_ABST
Patent Text Reader

Abstract

The invention provides an ultralight high-strength and high-plasticity dual-phase magnesium-lithium alloy as well as a preparation process and application thereof. The ultralight high-strength and high-plasticity dual-phase magnesium-lithium alloy comprises the following components in percentage by weight: 6.5 to 9.5 percent of Li, 1 to 5 percent of Al, 1 to 5 percent of Zn, 0.2 to 4 percent of RE (rare earth element), 0.2 to 1 percent of Ca and the balance of Mg. According to the preparation process, on the basis of a dual-phase Mg-Li-Al-Zn alloy system, preparation of the ultra-light high-strength and high-plasticity dual-phase magnesium-lithium alloy is achieved through the measures of adding double rare earth elements Gd and Y and a grain refining element Ca, optimizing smelting process parameters, heat treatment and composite deformation process parameters and the like. The magnesium-lithium alloy has excellent mechanical properties, is suitable for industrial production, and can meet the performance requirements required by magnesium-lithium alloy application in the fields of aerospace, traffic transportation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to alloy technology, and in particular to an ultra-light high-strength plastic dual-phase magnesium-lithium alloy, and a preparation process and application thereof. Background Art

[0002] With the rapid development of my country's economy and science and technology, there is an urgent need to solve the problem of lightweighting high-end equipment in major engineering application fields such as national defense, aviation, aerospace and transportation. Among them, material lightweighting is an important way to achieve a significant overall weight reduction of components. The density of magnesium-lithium alloy is only 1.35-1.65g / cm 3 , with high specific strength, high specific stiffness, strong vibration resistance, can withstand large load impact, plastic processing and good electromagnetic shielding performance, it is the best lightweight metal structural material. With the increase of Li content, magnesium-lithium alloys successively present α-Mg single-phase structure, α-Mg+β-Li two-phase structure, and β-Li single-phase structure. Among them, the single-phase α magnesium-lithium alloy has high strength but poor plasticity; the single-phase β magnesium-lithium alloy has good plasticity but low strength. In comparison, the two-phase magnesium-lithium alloy has achieved a more ideal balance between strength and plasticity, and is the focus of the development of lightweight materials. However, the two-phase magnesium-lithium alloy with a Li content higher than 6% still has the problem of low absolute strength, which seriously restricts the engineering application of the two-phase magnesium-lithium alloy.

[0003] Patent CN 115125423 A adopts a composite deformation process of forging-hot extrusion-hot rolling, and adds Ag and Zr as grain refiners to obtain a deformation structure with fine grains, and successfully prepares a two-phase Mg-Li-Al-Zn alloy with a strength of 300-350MPa. However, the cost of Ag is high, making it difficult to achieve large-scale industrial production. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of low absolute strength of dual-phase magnesium-lithium alloys with high lithium content, and to propose an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy with excellent mechanical properties and a density of 1.55-1.65 g / cm 3 The tensile strength is 300-360MPa, the yield strength is 280-340MPa, and the elongation is 12-25%. It is suitable for industrial production and can meet the performance requirements for magnesium-lithium alloy applications in aerospace, transportation and other fields.

[0005] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy includes the following components and contents: Li: 6.5-9.5wt.%, Al: 1-5wt.%, Zn: 1-5wt.%, RE (rare earth elements): 0.2-4wt.%, Ca: 0.2-1wt.%, and the balance is Mg.

[0007] Furthermore, the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy includes the following components and contents: Li: 7-8wt.%, Al: 2-4wt.%, Zn: 1-2wt.%, RE: 0.3-1wt.%, Ca: 0.2-0.5wt.%, and the balance is Mg.

[0008] Furthermore, the RE is Y and / or Gd.

[0009] Furthermore, the RE is preferably Y and Gd, and the usage ratio of the two is 1:1-4:1.

[0010] Furthermore, the usage ratio of Y to Gd is preferably 1:1-2:1.

[0011] Furthermore, the density of the ultra-light high-strength plastic dual-phase magnesium-lithium alloy is 1.55-1.65 g / cm 3 , tensile strength is 300-360MPa, yield strength is 280-340MPa, and elongation is 12-25%.

[0012] Another object of the present invention is to disclose a preparation process of an ultra-light high-strength and plastic dual-phase magnesium-lithium alloy. On the basis of the dual-phase Mg-Li-Al-Zn alloy system, by adding dual rare earth elements Gd and Y, grain refinement element Ca, optimizing smelting process parameters, heat treatment and composite deformation process parameters, etc., the preparation of high-strength and plastic magnesium-lithium alloy is achieved. Specifically, the process comprises the following steps:

[0013] Step 1, weighing raw materials pure Mg ingots, pure Li ingots, pure Al ingots, pure Zn ingots, Mg-RE and Mg-Ca master alloys according to mass fraction, grinding to remove the oxide layer on the surface of all raw materials, performing ultrasonic cleaning and vacuum preheating treatment, and wrapping the treated raw materials with aluminum foil for vacuum storage;

[0014] Step 2, placing the raw materials in a high vacuum electromagnetic induction melting furnace equipped with a mechanical stirring and mold heating device to melt the dual-phase magnesium-lithium alloy ingot;

[0015] Step 3, placing the dual-phase magnesium-lithium alloy ingot into a medium-temperature box-type resistance furnace for homogenization heat treatment, and immediately performing a solution water quenching treatment after the homogenization heat treatment is completed;

[0016] Step 4, subjecting the dual-phase magnesium-lithium alloy to multi-directional forging at a reduced temperature;

[0017] Step 5, subjecting the dual-phase magnesium-lithium alloy to variable temperature rapid extrusion;

[0018] Step 6: Roll the dual-phase magnesium-lithium alloy at room temperature to prepare an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy.

[0019] Furthermore, the purity of the raw materials and the aluminum foil in step 1 is greater than or equal to 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0020] Furthermore, in step 1, the content of RE in the Mg-RE is 10-30%, and the content of Ca in the Mg-Ca alloy is 10-30%.

[0021] Furthermore, the preheating treatment temperature in step 1 is 150-200° C. and the time is 0.5-2 h.

[0022] Furthermore, the smelting process of step 2 is as follows: firstly, the pure Mg ingot is placed in the smelting crucible, and the remaining raw materials are wrapped with aluminum foil and loaded into the secondary feeding bin, and the vacuum system is turned on to evacuate the vacuum, and the inert gas is backfilled during the evacuation process, and the furnace is washed repeatedly for 2-5 times until the vacuum is 1×10 -2 When the temperature is below 1 Pa, recharge 1-5×10 4 Pa inert gas is used to protect the smelting process; the circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 700-740°C, the secondary feeding port is opened to add pure Al ingots, pure Zn ingots, Mg-RE and Mg-Ca intermediate alloys, and after keeping warm for 10-20 minutes, the first mechanical stirring is carried out, and the mold heating device is started to preheat the mold; the temperature is reduced to 630-670°C, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10-20 minutes, and the second mechanical stirring is carried out, and the temperature is raised to 700-730°C for casting; the ingot is taken out after cooling to 150-200°C with the furnace, and air-cooled in a ventilated place.

[0023] Furthermore, the inert protective gas is selected from high-purity argon or CO2+SF6 protective gas, wherein the volume ratio of CO2 to SF6 is 50-100:1, the mechanical stirring speed is 300-600r / min, the time is 3-6min, the casting mold is selected from a copper mold, and the mold preheating temperature is 150-300°C.

[0024] Furthermore, in step 3, the homogenization heat treatment temperature is 240-280° C., the time is 4-6 hours, and the air cooling treatment is performed.

[0025] Furthermore, the solution treatment in step 3 is performed at a temperature of 350-400°C, for a time of 3-6 hours, and with water quenching.

[0026] Furthermore, the cooling multi-directional forging in step 4 is performed for 6-12 passes, and the forging process is: the axial direction of the ingot is the Z direction, and the mutually perpendicular radial directions are the X and Y directions respectively; the first pass is upsetting deformation along the Z direction, the second pass is drawing deformation along the X direction, and the third pass is drawing deformation along the Y direction. Every three passes is a cycle, the forging temperature of the first three passes is 260-320°C, and the temperature is reduced by 15-30°C for every subsequent three passes. The deformation amount of a single pass is 10-25%, and water quenching is performed every three passes.

[0027] Furthermore, the variable temperature rapid extrusion in step 5 is performed 2-3 times, and is performed in the temperature ranges of high temperature, low temperature and medium temperature in sequence, wherein the high temperature range is 300-400°C, the medium temperature range is 200-300°C, and the low temperature range is 100-200°C; the temperature of the first pass is in the high temperature range, the temperature of the second pass is in the medium temperature range, and the temperature of the third pass is in the low temperature range; the extrusion ratio of the first pass is 9:1-16:1, and the extrusion ratio of the subsequent pass is 16:1-45:1; the extrusion speed of the first pass is 6-10m / min, and the extrusion speed of the subsequent pass is 2-5m / min, and water quenching is performed in each pass.

[0028] Furthermore, the temperature of the room temperature rolling in step 6 is 20-40° C., the deformation amount of a single pass is 4-8%, and the total deformation amount is 30-50%.

[0029] Another object of the present invention is to disclose an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy for use in the fields of aerospace and transportation.

[0030] The ultra-light high-strength plastic dual-phase magnesium-lithium alloy of the present invention, its preparation process and use have the following advantages compared with the prior art:

[0031] 1) The present invention adopts a high vacuum electromagnetic induction melting method under inert gas protection to prepare a dual-phase Mg-Li-Al-Zn-Gd-Y-Ca magnesium-lithium alloy ingot, and multi-directional forging deformation refines the original cast large grains, accumulates distortion energy during the cooling forging process, and closes some casting defects. Variable temperature rapid extrusion deformation: The first extrusion mechanically crushes α-Mg, and a large amount of distortion energy is accumulated inside the β-Li phase; the subsequent cooling and large deformation extrusion completely crushes the α-Mg phase into a bamboo-like structure to achieve the effect of organizational refinement. The large amount of distortion energy inside the β-Li phase causes the recrystallization temperature to drop, induces dynamic recrystallization, and refines the grains. Each stage of deformation water quenching effectively prevents grain growth to obtain a refined α-Mg phase and a β-Li phase dynamic recrystallization structure, thereby improving mechanical properties. Subsequently, room temperature rolling is performed to introduce high-density dislocations and fine nano-equiaxed crystals into α-Mg to improve the work hardening effect. The release of high deformation energy inside the β-Li phase promotes the precipitation of nano-strengthening phases, further improving the strength.

[0032] 2) The ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy of the present invention introduces dual rare earth elements Gd and Y and grain-refining element Ca. The dual rare earth elements can form a hard reinforcing phase Al-RE (Y, Gd) at the β-Li phase boundary and within the phase, improve the strength of β-Li, coordinate the deformation of the two phases, and promote the dynamic recrystallization process of the β-Li phase during thermal deformation. The Ca element can effectively refine the α-Mg phase and weaken the basal texture. The dual rare earth plus Ca elements significantly improve the plasticity of the deformed dual-phase magnesium-lithium alloy, further enhance the strengthening effect of deformation on the magnesium-lithium alloy, and achieve a synergistic improvement in the strength and plasticity of the dual-phase magnesium-lithium alloy.

[0033] 3) The ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy of the present invention further enhances the strengthening effect of the composite deformation process on the performance of the magnesium-lithium alloy on the basis of alloying with the addition of dual rare earth and calcium elements. A rare earth second phase and nano-strengthening phase with high strength are formed, and the coupling mechanism of solid solution strengthening, fine grain strengthening and dislocation strengthening is achieved. The strength of the magnesium-lithium alloy is greatly improved through the composite deformation process of cooling forging, variable temperature extrusion and room temperature rolling, overcoming the problem of weak strengthening effect of single extrusion, rolling and other deformation processes. On this basis, the content of dual rare earth elements Gd, Y and Ca is regulated, the content, size and distribution of rare earth strengthening phases in the deformed dual-phase magnesium-lithium alloy are optimized, the precipitation of nano-MgLi2Al strengthening phases is promoted, the α-Mg basal texture is weakened, the two-phase structure is refined, and the plastic loss of the magnesium-lithium alloy during the composite deformation process is greatly reduced.

[0034] 4) The density of the ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy of the present invention is 1.55-1.65 g / cm 3 , tensile strength is 300-360MPa, yield strength is 280-340MPa, and elongation is 12-25%.

[0035] In summary, the preparation process of the ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy of the present invention is simple, efficient, low-cost and pollution-free. The prepared ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy has excellent mechanical properties, is suitable for industrial production, and can meet the performance requirements for the application of magnesium-lithium alloys in the fields of aerospace, transportation and machinery manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 1 is the tensile stress-strain curve in the embodiments and comparative examples. DETAILED DESCRIPTION

[0037] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0038] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0039] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0040] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0041] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0042] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0043] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0044] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0045] Embodiment 1:

[0046] This embodiment discloses an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, the remainder is magnesium, and the total impurity content is less than 0.01wt.%.

[0047] Step 1. Weigh the raw materials pure Mg ingots, pure Li ingots, pure Al ingots, pure Zn ingots, Mg-20Y, Mg-20Gd and Mg-20Ca master alloys according to their mass fractions. The purity of the raw materials is 99.99wt.%, and the oxide layer on the surface of all raw materials is removed by grinding. The raw materials are ultrasonically cleaned and preheated at a temperature of 150°C for 1 hour. The treated raw materials are wrapped in aluminum foil for vacuum storage.

[0048] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al, Zn ingots and intermediate alloys, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0049] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0050] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0051] Step 5: subject the forged dual-phase magnesium-lithium alloy to variable temperature rapid extrusion deformation, the first extrusion ratio is 16:1, the extrusion temperature is 350°C, the extrusion speed is 8m / min, the second extrusion ratio is 32:1, the extrusion temperature is 250°C, the extrusion speed is 4m / min, and the alloy is quickly water quenched after extrusion.

[0052] Step 6: rolling the extruded dual-phase magnesium-lithium alloy at room temperature, wherein the temperature of room temperature rolling is 25° C., the deformation amount of a single pass is 6%, and the total deformation amount is 40%.

[0053] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Example 1 was found to be 1.57 g / cm 3 , the tensile strength is 335MPa, the yield strength is 309MPa, and the elongation is 16.1%.

[0054] Embodiment 2:

[0055] This embodiment discloses an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 9wt.%, Al: 5wt.%, Zn: 3wt.%, Y: 1.2wt.%, Gd: 0.4wt.%, Ca: 0.8wt.%, the remainder is magnesium, and the total impurity content is less than 0.01wt.%.

[0056] Step 1. Weigh the raw materials pure Mg ingots, pure Li ingots, pure Al ingots, pure Zn ingots, Mg-20Y, Mg-20Gd and Mg-20Ca master alloys according to their mass fractions. The purity of the raw materials is 99.99wt.%, and the oxide layer on the surface of all raw materials is removed by grinding. The raw materials are ultrasonically cleaned and preheated at a temperature of 150°C for 1 hour. The treated raw materials are wrapped in aluminum foil for vacuum storage.

[0057] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4 Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al, Zn ingots and intermediate alloys, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0058] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0059] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0060] Step 5: subject the forged dual-phase magnesium-lithium alloy to variable temperature rapid extrusion deformation, the first extrusion ratio is 16:1, the extrusion temperature is 350°C, the extrusion speed is 8m / min, the second extrusion ratio is 32:1, the extrusion temperature is 250°C, the extrusion speed is 4m / min, and the alloy is quickly water quenched after extrusion.

[0061] Step 6: rolling the extruded dual-phase magnesium-lithium alloy at room temperature, wherein the temperature of room temperature rolling is 25° C., the deformation amount of a single pass is 6%, and the total deformation amount is 40%.

[0062] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Example 2 was found to be 1.57 g / cm 3 , the tensile strength is 341MPa, the yield strength is 311MPa, and the elongation is 13.3%.

[0063] Embodiment 3:

[0064] This embodiment discloses an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 7wt.%, Al: 4wt.%, Zn: 4wt.%, Y: 2wt.%, Gd: 0.5wt.%, Ca: 0.6wt.%, the remainder is magnesium, and the total impurity content is less than 0.01wt.%.

[0065] Step 1. Weigh the raw materials pure Mg ingots, pure Li ingots, pure Al ingots, pure Zn ingots, Mg-20Y, Mg-20Gd and Mg-20Ca master alloys according to their mass fractions. The purity of the raw materials is 99.99wt.%, and the oxide layer on the surface of all raw materials is removed by grinding. The raw materials are ultrasonically cleaned and preheated at a temperature of 150°C for 1 hour. The treated raw materials are wrapped in aluminum foil for vacuum storage.

[0066] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4 Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al, Zn ingots and intermediate alloys, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0067] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0068] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0069] Step 5: subject the forged dual-phase magnesium-lithium alloy to variable temperature rapid extrusion deformation, the first extrusion ratio is 16:1, the extrusion temperature is 350°C, the extrusion speed is 8m / min, the second extrusion ratio is 32:1, the extrusion temperature is 250°C, the extrusion speed is 4m / min, and the alloy is quickly water quenched after extrusion.

[0070] Step 6: rolling the extruded dual-phase magnesium-lithium alloy at room temperature, wherein the temperature of room temperature rolling is 25° C., the deformation amount of a single pass is 6%, and the total deformation amount is 40%.

[0071] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Example 3 was found to be 1.57 g / cm 3 , the tensile strength is 330MPa, the yield strength is 302MPa, and the elongation is 15.5%.

[0072] Comparative Example 1:

[0073] This comparative example discloses a dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0074] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd and Mg-20Ca master alloy according to mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment at a preheating temperature of 150°C for 1 hour, and wrap the treated raw materials with aluminum foil for vacuum storage.

[0075] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al, Zn ingots and intermediate alloys, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0076] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 1 was found to be 1.57 g / cm 3 , the tensile strength is 201MPa, the yield strength is 165MPa, and the elongation is 29.1%.

[0077] Comparative Example 2:

[0078] This comparative example discloses an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0079] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd and Mg-20Ca master alloy according to mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment at a preheating temperature of 150°C for 1 hour, and wrap the treated raw materials with aluminum foil for vacuum storage.

[0080] Step 2: Take out the raw material Mg ingot and put it into the high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. Start the vacuum system to evacuate. During the vacuuming process, backfill with argon gas. Repeat the furnace cleaning three times until the vacuum reaches 9×10 -3 Pa and then charge 2×10 4Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al, Zn ingots and intermediate alloys, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0081] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0082] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0083] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 2 was found to be 1.57 g / cm 3 , the tensile strength is 243MPa, the yield strength is 211MPa, and the elongation is 21.6%.

[0084] Comparative Example 3:

[0085] This comparative example discloses an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0086] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd and Mg-20Ca master alloy according to mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment at a preheating temperature of 150°C for 1 hour, and wrap the treated raw materials with aluminum foil for vacuum storage.

[0087] Step 2: Take out the raw material Mg ingot and put it into the high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. Start the vacuum system to evacuate. During the vacuuming process, backfill with argon gas. Repeat the furnace cleaning three times until the vacuum reaches 9×10 -3 Pa and then charge 2×10 4 Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al, Zn ingots and intermediate alloys, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0088] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0089] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0090] Step 5: subject the forged dual-phase magnesium-lithium alloy to variable temperature rapid extrusion deformation, the first extrusion ratio is 16:1, the extrusion temperature is 350°C, the extrusion speed is 8m / min, the second extrusion ratio is 32:1, the extrusion temperature is 250°C, the extrusion speed is 4m / min, and the alloy is quickly water quenched after extrusion.

[0091] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 3 was found to be 1.57 g / cm 3 , the tensile strength is 285MPa, the yield strength is 257MPa, and the elongation is 20.1%.

[0092] Comparative Example 4:

[0093] This comparative example discloses a dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0094] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y and Mg-20Gd master alloy according to mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment at a preheating temperature of 150°C for 1 hour, and wrap the treated raw materials with aluminum foil for vacuum storage.

[0095] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4 Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al and Zn ingots, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0096] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0097] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0098] Step 5: hot extrude the two-phase magnesium-lithium alloy after solid solution, with an extrusion temperature of 280° C., an extrusion ratio of 32:1, and an extrusion speed of 0.5 m / min, and quickly water quench the alloy after extrusion.

[0099] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 4 was found to be 1.57 g / cm 3 , the tensile strength is 266MPa, the yield strength is 234MPa, and the elongation is 17.9%.

[0100] Comparative Example 5:

[0101] This comparative example discloses a dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0102] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y and Mg-20Gd master alloy according to mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment at a preheating temperature of 150°C for 1 hour, and wrap the treated raw materials with aluminum foil for vacuum storage.

[0103] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4 Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al and Zn ingots, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0104] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0105] Step 4: hot extrude the two-phase magnesium-lithium alloy after solid solution, with an extrusion temperature of 280° C., an extrusion ratio of 32:1, and an extrusion speed of 0.5 m / min, and quickly water quench the alloy after extrusion.

[0106] Step 5: The extruded dual-phase magnesium-lithium alloy is rolled at room temperature at a temperature of 25° C., a single-pass deformation of 6%, and a total deformation of 40%.

[0107] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 5 was found to be 1.57 g / cm 3 , the tensile strength is 279MPa, the yield strength is 255MPa, and the elongation is 12.6%.

[0108] Comparative Example 6:

[0109] This comparative example discloses a dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0110] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot and pure Zn ingot according to the mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment at a preheating temperature of 150°C for 1 hour, and wrap the treated raw materials with aluminum foil for vacuum storage.

[0111] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4 Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al and Zn ingots, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0112] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0113] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0114] Step 5: subject the forged dual-phase magnesium-lithium alloy to variable temperature rapid extrusion deformation, the first extrusion ratio is 16:1, the extrusion temperature is 350°C, the extrusion speed is 8m / min, the second extrusion ratio is 32:1, the extrusion temperature is 250°C, the extrusion speed is 4m / min, and the alloy is quickly water quenched after extrusion.

[0115] Step 6: rolling the extruded dual-phase magnesium-lithium alloy at room temperature, wherein the temperature of room temperature rolling is 25° C., the deformation amount of a single pass is 6%, and the total deformation amount is 40%.

[0116] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 6 was found to be 1.56 g / cm 3 , the tensile strength is 289MPa, the yield strength is 257MPa, and the elongation is 6.7%.

[0117] Comparative Example 7:

[0118] This comparative example discloses a dual-phase magnesium-lithium alloy, the composition and mass fraction of each element of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.5wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0119] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot and Mg-20Y master alloy according to mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment, the preheating temperature is 150°C, the time is 1h, and the treated raw materials are wrapped with aluminum foil for vacuum storage.

[0120] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al and Zn ingots, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0121] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0122] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0123] Step 5: subject the forged dual-phase magnesium-lithium alloy to variable temperature rapid extrusion deformation, the first extrusion ratio is 16:1, the extrusion temperature is 350°C, the extrusion speed is 8m / min, the second extrusion ratio is 32:1, the extrusion temperature is 250°C, the extrusion speed is 4m / min, and the alloy is quickly water quenched after extrusion.

[0124] Step 6: rolling the extruded dual-phase magnesium-lithium alloy at room temperature, wherein the temperature of room temperature rolling is 25° C., the deformation amount of a single pass is 6%, and the total deformation amount is 40%.

[0125] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 7 was found to be 1.57 g / cm 3 , the tensile strength is 315MPa, the yield strength is 290MPa, and the elongation is 12.7%.

[0126] Comparative Example 8:

[0127] This comparative example discloses a dual-phase magnesium-lithium alloy, the element composition and mass fraction of which are: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, and the balance is magnesium. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%.

[0128] Step 1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y and Mg-20Gd master alloy according to mass fraction, polish and remove the oxide layer on the surface of all raw materials, perform ultrasonic cleaning and preheating treatment at a preheating temperature of 150°C for 1 hour, and wrap the treated raw materials with aluminum foil for vacuum storage.

[0129] Step 2: Take out the raw material Mg ingot and put it into a high vacuum electromagnetic induction melting crucible. The rest of the raw materials are loaded into the secondary feeding bin. The vacuum system is turned on to evacuate the vacuum. During the evacuation process, argon is backfilled. The furnace is washed three times to evacuate to a vacuum of 9×10 -3 Pa and then charge 2×10 4 Pa argon gas is used to protect the smelting process. The circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 720℃, the secondary feeding port is opened to add pure Al and Zn ingots, and after keeping warm for 15 minutes, the first mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the mold heating device is started to preheat the copper mold at a preheating temperature of 200℃. The temperature is reduced to 650℃, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10 minutes. The second mechanical stirring is carried out at a speed of 400r / min for 3 minutes, and the temperature is raised to 720℃ for casting. The ingot is taken out after cooling to 180℃ with the furnace, and air-cooled in a ventilated place.

[0130] Step 3: Place the dual-phase magnesium-lithium alloy ingot in a medium-temperature box-type resistance furnace for homogenization heat treatment and solution treatment, wherein the homogenization treatment temperature is 250°C, the time is 4 hours, and the air cooling treatment is carried out. The solution treatment temperature is 350°C, the time is 4 hours, and the water quenching treatment is carried out.

[0131] Step 4: Place the solid solution dual-phase magnesium-lithium alloy in a resistance furnace for preheating for 1 hour, and then perform 9 cooling multi-directional forgings. The forging temperature of the first 3 passes is 280°C, and the temperature is reduced by 20°C for every 3 subsequent passes. The alloy is placed in a resistance furnace for insulation for 30 minutes, with a single pass deformation of 15%, and water quenching.

[0132] Step 5: subject the forged dual-phase magnesium-lithium alloy to variable temperature rapid extrusion deformation, the first extrusion ratio is 16:1, the extrusion temperature is 350°C, the extrusion speed is 8m / min, the second extrusion ratio is 32:1, the extrusion temperature is 250°C, the extrusion speed is 4m / min, and the alloy is quickly water quenched after extrusion.

[0133] Step 6: rolling the extruded dual-phase magnesium-lithium alloy at room temperature, wherein the temperature of room temperature rolling is 25° C., the deformation amount of a single pass is 6%, and the total deformation amount is 40%.

[0134] Through density and tensile mechanical property tests, the density of the dual-phase magnesium-lithium alloy in Comparative Example 8 was found to be 1.57 g / cm 3 , the tensile strength is 326MPa, the yield strength is 297MPa, and the elongation is 14.9%.

[0135] By comparing Examples 1, 2, and 3, it is found that the optimal strength and plasticity are within the preferred composition range. Compared with the cast state of Comparative Example 1 and the single forging state of Comparative Example 2, the strength of the composite deformation of the examples is significantly improved, and the tensile strength of the alloy in the multi-directional forging + variable temperature extrusion + room temperature rolling state of Example 1 is 17.1% higher than that of the alloy in the multi-directional forging + variable temperature extrusion state of Comparative Example 3, and the plasticity is only reduced by 4%. Figure 1 As shown. In addition, compared with the multi-directional forging + conventional extrusion of comparative example 4 and the conventional extrusion + room temperature rolling of comparative example 5, the strength of the alloy in the multi-directional forging + variable temperature extrusion + room temperature rolling state of the embodiment is increased by 50-70MPa, and the plasticity has no obvious decrease. Therefore, the strength and plasticity of the present invention are significantly improved compared with the traditional single deformation process or the composite deformation process. According to the tensile curves of Example 1 and Comparative Examples 6, 7, and 8, it can be found that the plasticity of the two-phase Mg-Li-Al-Zn matrix without the addition of rare earth elements decreases significantly after composite deformation, which is only 6.7%. After the addition of rare earth elements, both strength and plasticity are improved. After the addition of Y, the strength is increased by 9.3%, and the plasticity is increased by 6%. After the addition of Gd and Y double rare earth elements, the strength is increased by 12.8%, and the plasticity is increased by 8.2%. The co-addition of Gd, Y double rare earth and Ca elements has the best strength and plasticity. Compared with the addition of double rare earth elements, the strength can be increased by 10-20MPa, and the plasticity can be increased by 3-5%, achieving a synergistic improvement of strength and plasticity under composite deformation. Combined with the above results, it can be seen that the strength of the dual-phase magnesium-lithium alloy is greatly improved after composite deformation. The addition of dual rare earth elements Gd, Y and Ca further improves the strength of the composite deformed magnesium-lithium alloy and significantly improves the plasticity, ultimately obtaining an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy.

[0136] In summary, the present invention can significantly refine the microstructure of the dual-phase magnesium-lithium alloy and achieve a synergistic improvement in the strength and plasticity of the dual-phase magnesium-lithium alloy. It has high preparation efficiency and can be suitable for industrial production.

[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy, characterized in that: The components and contents included are: Li: 6.5-9.5wt.%, Al: 1-5wt.%, Zn: 1-5wt.%, RE: 0.2-4wt.%, Ca: 0.2-1wt.%, and the balance is Mg.

2. The ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 1, characterized in that: The RE is Y and / or Gd.

3. A process for preparing the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 1 or 2, characterized in that: The following steps are involved: Step 1, weighing raw materials pure Mg ingots, pure Li ingots, pure Al ingots, pure Zn ingots, Mg-RE and Mg-Ca master alloys according to mass fraction, grinding to remove the oxide layer on the surface of all raw materials, performing ultrasonic cleaning and vacuum preheating treatment, and wrapping the treated raw materials with aluminum foil for vacuum storage; Step 2, placing the raw materials in a high vacuum electromagnetic induction melting furnace equipped with a mechanical stirring and mold heating device to melt the dual-phase magnesium-lithium alloy ingot; Step 3, placing the dual-phase magnesium-lithium alloy ingot into a medium-temperature box-type resistance furnace for homogenization heat treatment, and immediately performing a solution water quenching treatment after the homogenization heat treatment is completed; Step 4, subjecting the dual-phase magnesium-lithium alloy to multi-directional forging with cooling; Step 5, subjecting the dual-phase magnesium-lithium alloy to variable temperature rapid extrusion; Step 6: Roll the dual-phase magnesium-lithium alloy at room temperature to prepare an ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy.

4. The preparation process of the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 3 is characterized in that: Step 1: the content of RE in the Mg-RE is 10-30%, and the content of Ca in the Mg-Ca alloy is 10-30%; And / or, the preheating treatment temperature in step 1 is 150-200° C. and the time is 0.5-2 h.

5. The preparation process of the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 3 is characterized in that: Step 2: The smelting process is as follows: first, put the pure Mg ingot into the smelting crucible, and then wrap the remaining raw materials with aluminum foil and load them into the secondary feeding bin. Then, start the vacuum system to evacuate the vacuum, and then backfill with inert gas during the evacuation process. Repeat the furnace cleaning for 2-5 times until the vacuum reaches 1×10 -2 When the temperature is below 1 Pa, recharge 1-5×10 4 Pa inert gas is used to protect the smelting process; the circulating water cooling system and the electromagnetic induction melting furnace heating system are turned on, the smelting temperature is raised to 700-740°C, the secondary feeding port is opened to add pure Al ingots, pure Zn ingots, Mg-RE and Mg-Ca intermediate alloys, and after keeping warm for 10-20 minutes, the first mechanical stirring is carried out, and the mold heating device is started to preheat the mold; the temperature is reduced to 630-670°C, the secondary feeding port is opened to add pure Li ingots, and the temperature is kept warm for 10-20 minutes, and the second mechanical stirring is carried out, and the temperature is raised to 700-730°C for casting; the ingot is taken out after cooling to 150-200°C with the furnace, and air-cooled in a ventilated place.

6. The preparation process of the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 3 is characterized in that: The homogenization heat treatment temperature in step 3 is 240-280°C, the time is 4-6h, and the air cooling treatment is performed; And / or, the solution temperature is 350-400°C, the time is 3-6h, and the water quenching treatment is performed.

7. The preparation process of the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The cooling multi-directional forging in step 4 is performed for 6-12 times, and the forging process is: the axial direction of the ingot is the Z direction, and the mutually perpendicular radial directions are the X and Y directions respectively; the first pass is the upsetting deformation along the Z direction, the second pass is the drawing deformation along the X direction, and the third pass is the drawing deformation along the Y direction. Every three passes is a cycle, and the forging temperature of the first three passes is 260-320°C. For every subsequent three passes, the temperature is reduced by 15-30°C, the deformation amount of a single pass is 10-25%, and water quenching is performed every three passes.

8. The preparation process of the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 3 is characterized in that: The variable temperature rapid extrusion in step 5 is performed 2-3 times, and is performed in the temperature range of high temperature, low temperature and medium temperature in sequence, wherein the high temperature range is 300-400°C, the medium temperature range is 200-300°C, and the low temperature range is 100-200°C; the first pass temperature selects the high temperature range, the second pass temperature selects the medium temperature range, and the third pass selects the low temperature range; the first pass extrusion ratio is 9:1-16:1, and the subsequent pass extrusion ratio is 16:1-45:1; the first pass extrusion speed is 6-10m / min, and the subsequent pass extrusion speed is 2-5m / min, and each pass is water quenched.

9. The preparation process of the ultra-light high-strength and plastic dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The temperature of room temperature rolling in step 6 is 20-40° C., the deformation amount of a single pass is 4-8%, and the total deformation amount is 30-50%.

10. Use of the ultra-light, high-strength and plastic dual-phase magnesium-lithium alloy according to claim 1 or 2 in the fields of aerospace and transportation.

Citation Information

Patent Citations

  • High-strength and high-formability magnesium-lithium alloy as well as preparation method and application thereof

    CN115125423A